Dominions Trade Union Conference, 1943 (United Kingdom, 1943)
1943 1939-1945 "Dominions Trade Union Conference, 1943" [HFR0028], 1943 The TUC organised a conference April 12-16 1943 for delegates from trade union centres in the Dominions [self-governing territories in the British Empire]. The principal subjects discussed were rationing and curtailment of supplies, production committees, trade unions in the war, and issues relating to post-war reconstruction and international trade union organisation. After the conference, the delegates toured a number of war factories and shipbuilding yards. Many of the posters shown in this photograph are now in the TUC Collections.